Answer:
It cannot be solved furthur bro as the value of x is unspecified
Answer:
x = -(h+g) / f
Step-by-step explanation:
-fx - g = h
-fx = h + g
x = (h + g) / -f
x = -(h+g)/f
R(s + t) = st
Rs + Rt = st
Rs - st = -Rt
s ( R - t) = -Rt
*s = - Rt / (R - t) Multiply through by -1 on the right.
*s = Rt / (t - R) Put in the brackets in your answer. What you have been writing means
s = Rt/r - R you need the brackets. The stars mean that either could be an answer. I think your problem could be the brackets. Now I'm reasonably certain this is correct.